2021
DOI: 10.1101/2021.08.24.457572
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mismatch repair deficiency is not sufficient to increase tumor immunogenicity

Abstract: DNA mismatch repair deficiency (MMRd) in human cancer is associated with high tumor mutational burden (TMB), frameshift mutation-derived neoantigens, increased T cell infiltration, and remarkable responsiveness to immune checkpoint blockade (ICB) therapy. Nevertheless, about half of MMRd tumors do not respond to ICB for unclear reasons. While tumor cell line transplant models of MMRd have reinforced the importance of TMB in immune response, critical questions remain regarding the role of immunosurveillance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 78 publications
(124 reference statements)
0
10
0
Order By: Relevance
“…Additionally, the complex TME in GEMMs, a pertinent reflection of the patient tumor, makes it difficult to say with certainty that the impact of glutaminase inhibition in the CD8 T cells alone was responsible for their impeded function, and not a result of the cross talk within cells of the TME. Finally, given that KEAP1 and STK11 mutant lung adenocarcinoma are generally associated with cigarette smoke and high tumor mutational burden (TMB) (Ricciuti et al, 2022;Skoulidis et al, 2015), it will be important to validate these findings in murine models engineered to exhibit a higher TMB and/or neoantigens (Fitzgerald et al, 2021;Westcott et al, 2021). Despite this, our findings suggest that glutaminase function must be unimpeded in CD8 T cells to ensure that they have the ability to reach their full cytotoxic potential.…”
Section: Limitations Of the Studymentioning
confidence: 91%
“…Additionally, the complex TME in GEMMs, a pertinent reflection of the patient tumor, makes it difficult to say with certainty that the impact of glutaminase inhibition in the CD8 T cells alone was responsible for their impeded function, and not a result of the cross talk within cells of the TME. Finally, given that KEAP1 and STK11 mutant lung adenocarcinoma are generally associated with cigarette smoke and high tumor mutational burden (TMB) (Ricciuti et al, 2022;Skoulidis et al, 2015), it will be important to validate these findings in murine models engineered to exhibit a higher TMB and/or neoantigens (Fitzgerald et al, 2021;Westcott et al, 2021). Despite this, our findings suggest that glutaminase function must be unimpeded in CD8 T cells to ensure that they have the ability to reach their full cytotoxic potential.…”
Section: Limitations Of the Studymentioning
confidence: 91%
“…We then examined subclonal neoantigen complexity. Recent data from preclinical models 25 as well as patient cohorts 26 suggest that an increased number of subclonal neoantigens can drive early immune exhaustion and lack of checkpoint inhibitor treatment response. We find that subclones carrying either MSH6 F1088fs or MSH3 K383fs indels show a greater proportion of subclonal predicted neoantigens ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A mutator strategy exacerbates intratumour heterogeneity and increases subclonal neo-antigen burden. Recent preclinical studies indicate that increased subclonal complexity and subclonal neoantigen burdens blunt immune responses to checkpoint inhibitors in MMRd animal models due to immune exhaustion 25 . In line with this, we have recently found that low neoantigen clonality predicts lack of response to checkpoint inhibitors in MMRd patients 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Tumours are often composed of a myriad of distinct cancer subclones, which may harbour distinct sets of mutations affecting sensitivity or resistance to therapy. Emerging work suggests that clonal neoantigens may elicit a more sustained and effective immune response [97]. Less heterogeneous tumours derived by single-cell cloning of cells from a UVB radiation-exposed melanoma cell line, which had a lower number of tumour subclones than their parental cells, were shown to exhibit increased immunogenicity and slower tumour growth [98].…”
Section: Predicting Immunotherapy Responsementioning
confidence: 99%